Constructive and destructive leadership behaviors, skills, styles and traits in BIM-based construction projects - Omer, Mazen Mohamed Alkhdar; Nik Muhammad Adeeq, Mohd Ezazee; Lee, Yong Siang; Rajabi, Mohammad Sadra; Abdul Rahimi, Abdul Rahman (MDPI, 2022)
Building information modeling (BIM) implementation is expanding over time, and collaboration is becoming more critical in construction projects. Leadership characteristics may contribute to or hinder the effectiveness of these collaborations in BIM-based construction projects. However, the current body of knowledge lacks information on the leadership characteristics that can be constructive or destructive for BIM-based construction projects. Therefore, this study aims to determine the constructive and destructive leadership behaviors, skills, styles, and traits in BIM-based construction projects. An explorative qualitative study was conducted by interviewing twenty architecture, engineering, and construction (AEC) professionals. Then, the thematic analysis approach was used to analyze the interview data. The study findings suggest that common constructive leadership behaviors are tolerant and committed. Furthermore, the common constructive leadership trait and style is reliability. On the contrary, the common destructive leadership behavior is intolerant. This study provides the literature with a novel list of constructive and destructive leadership characteristics for BIM-based construction projects. Understanding these characteristics would assist industry professionals and policymakers in increasing the performance of BIM-based construction projects.